Optimasi Perencanaan Jaringan LTE FDD 1800 MHz Di Kota Pekanbaru - M Arif Syiaruddin; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
LTE is a cellular technology developed by 3GPP which has improved from the previous mobile technologies. The implementation of LTE in Indonesia is still not evenly distributed and only for big cities. Hence, it takes some planning and a deeper study for the area that will be implemented by LTE network. Planning and network optimization is necessary in order to meet consumer needs of the LTE network. There are different ways of optimization methods can be used, in previous studies used a joint base station technique, optimization in other research done by changing basic parameters such as replacing the feeder cable and the addition site. In this study optimization techniques used by changing the type of modulation thus affecting the utilization values of SNR. The simulation results based on two scenarios i.e the number of sites for scenario 1in the total of 479 sites, while for scenario 2 indicates number of sites . in the mean time for a signal level coverage for scenario 1 and scenario 2 show -90 dBm and -95 dBm, respectively.Keywords : LTE, Optimization, Modulation, SINR.